Caring Perawat dengan Stres Hospitalisasi pada Anak Pra Sekolah di Ruang Rawat Inap Anak - Listiana, Ridya; Kustriyani, Menik; Sakti Widyaningsih, Tri (Jurnal Ilmiah Ners Indonesia, 2021)
Child care in hospital results in children having to be separated from their environment, resulting in children experiencing stress, to prevent severe stress involving the role of nurses in caring for children during hospitalization. The purpose of this study was to determine the relationship between nurse caring and hospitalization stress in pre-school children. This type of research is quantitative associative with a cross sectional approach. Sampling with consecutive sampling technique as many as 38 respondents. Researchers conducted an ethical test at RSUD Batang. Respondents were given an explanation and filled out informed consent before the study. The researcher guarantees the confidentiality of the respondents from the beginning to the end of the study. The study was conducted in July 2020 at RSUD Batang . The research instrument uses a questionnaire sheet. Univariate data analysis is presented in the Frequency Distribution table and the research data were analyzed using the Spearman Rank test with p value = 0.000 with r value = -0.639. The results of this study showed that there was a relationship between nurse caring and hospitalization stress in pre-school children in the inpatient room. Abstrak Perawatan anak di rumah sakit mengakibatkan anak harus berpisah dengan lingkungannya sehingga mengakibatkan anak mengalami stres, untuk mencegah stres yang berat melibatkan peran perawat dalam merawat anak selama menjalani hospitalisasi.tujuan penelitian ini mengetahui hubungan caring perawat dengan stres hospitalisasi pada anak pra sekolah. Jenis penelitian ini adalah kuantitatif assosiatif dengan pendekatan cross sectional. Pengambilan sampel dengan teknik consecutive sampling sebanyak 38 responden. Peneliti melakukan uji etik di RSUD Batang. Responden diberikan penjelasan dan mengisi informed consent sebelum penelitian. Peneliti menjamin kerahasiaan responden mulai dari awal sampai akhir penelitian. Penelitian dilakukan pada bulan Juli 2020 di RSUD Batang.Instrumen penelitian menggunakan lembar kuesioner. Analisa data univariat disajikan dalam tabel Distribusi Frekuensi dan data hasil penelitian dianalisis menggunakan uji Rank Spearman dengan hasil p value = 0,000 dengan nilai r hitung = -0,639. Hasil penelitian ini ada hubungan caring perawat dengan stres hospitalisasi pada anak pra sekolah di ruang rawat inap. Kata Kunci : caring perawat, stres hospitalisasi, anak pre sekolah